How to: Establish and run a stool bank. (December 2017) - Terveer, E.M.; van Beurden, Y.H.; Goorhuis, A.; Seegers, J.F.M.L.; Bauer, M.P.; van Nood, E.; Dijkgraaf, M.G.W.; Mulder, C.J.J.; Vandenbroucke-Grauls, C.M.J.E.; Verspaget, H.W.; Keller, J.J.; Kuijper, E.J.
Abstract: Background: Since 2013, several stool banks have been developed following publications reporting on clinical success of 'faecal microbiota transplantation' (FMT) for recurrent Clostridium difficile infections (CDI). However, protocols for donor screening, faecal suspension preparation, and transfer of the faecal suspension differ between countries and institutions. Moreover, no European consensus exists regarding the legislative aspects of the faecal suspension product. Internationally standardized recommendations about the above mentioned aspects have not yet been established. Objective: In 2015, the Netherlands Donor Feces Bank (NDFB) was founded with the primary aim of providing a standardized product for the treatment of patients with recurrent CDI in the Netherlands. Standard operation procedures for donor recruitment, donor selection, donor screening, and production, storage, and distribution of frozen faecal suspensions for FMT were formulated. Results and discussion: Our experience summarized in this review addresses current donor recruitment and screening, preparation of the faecal suspension, transfer of the faecal microbiota suspension, and the experiences and follow-up of the patients treated with donor faeces from the NDFB.